Tiempo del relato y perspectiva narrativa en la literatura en primera persona - Cuasante Fernández, Elena (Verbum – Analecta Neolatina, 2013)
Using as a base relevant studies on narrative theory and specific studies related to the autobiographical genre, this work sets out to perform a detailed analysis of the formal features of first person narratives. To be more concise, we have centred our analysis on two narrative categories that are most relevant to the autobiographical genre, that is, narrative tense and narrative perspective. The final objective of this study is to identify the dominant formal features of each variant of the autobiographical genre, and, to do this, we shall consider, on the one hand, the range within the genre, and on the other handmake a distinction between fiction and non-fiction.